Joint Pain an Agony of Life - Rheumatoid Arthritis & Alternative Medicines (Homoeopathy for All, 2022)
Rheumatoid arthritis (RA) is a  chronic disease in which various  joints in the body are inflamed,  leading to swelling, pain,  stiffness, and the possible loss of  function. The word arthritis means  inflammation of the joint (“arthr”  meaning joint and “itis” meaning  inflammation). Inflammation is  a medical term describing pain,  stiffness, redness and swelling.  Homoeopathy is a remarkable  resource for those dealing with joint  disorders. This article provides  an overview of the aetiology,  diagnosis, and appropriate general  & homoeopathic management of  this disorder.
Keywords: stiffness; aetiology; diagnosis